Education and wage inequality in Portugal - Neves, Henrique Robles Machado Duarte (2021)
The main goal of this Master’s thesis is to identify the impact of education on changes in the Portuguese wage distribution using quantile regression methods. I explore the counterfactual decomposition method proposed by Machado and Mata(2005) to decompose changes in the wage distribution from 1994 to 2018 into the factors contributing to those changes: composition effects (characteristics of the Portuguese working force) and structural effects (returns to those characteristics).The results show that education was a key factor contributing to higher wages but also greater wage inequality.